33.5k views
0 votes
4 m - 17/ m^2 - 16 + 3 m - 11/ m^2 - 16

User RikiRiocma
by
5.8k points

2 Answers

0 votes


\frac{4m - 17}{ {m}^(2) - 16 } + \frac{3m - 11}{ {m}^(2) - 16 } \\ \\ = \: \frac{7m - 28}{ {m}^(2) - 16 } \: \: = \: \: (7(m - 4))/((m + 4)(m - 4)) \\ \\ = \: \: (7)/(m + 4) \: \: (where \: m \: is \: not \: equal \: to \: 4)
User Gico
by
5.7k points
3 votes

(4m-17)/(m^(2)-16) + (3m - 11)/(m^(2)-16) = (4m-17+3m - 11)/(m^(2)-16) = (7m-28)/(m^(2)-16) = (7(m-4))/((m-4)(m+4)) = (7)/(m+4) When (m-4) \\eq 0 , m \\eq 4.
User Galadog
by
6.2k points